1991
DOI: 10.1104/pp.96.2.418
|View full text |Cite
|
Sign up to set email alerts
|

Elongation and Termination Reactions of Protein Synthesis on Maize Root Tip Polyribosomes Studied in a Homologous Cell-Free System

Abstract: We show that the control of gene expression at the level of elongation and termination of protein synthesis can be observed in vitro. Free cytoplasmic polyribosomes were isolated from maize (Zea mays) root tips, and translated in root tip extracts that had been fractionated with ammonium sulfate to contain elongation factors, and be depleted in initiation factors. The root tip extract performs elongation and termination reactions as efficiently as wheat germ extracts. The translation products of the maize syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…It was found using cytosolic extracts of Xenopus oocytes that the rates of in vitro translation at pH 7.0 and 6.8 were reduced by approximately 15% and 65%, respectively, relative to pH 7.3 (Grandin and Charbonneau, 1989). Furthermore, a strong pH dependence of protein synthesis has been shown in polyribosome preparations from maize root tips by Webster et al (1991), who suggested that the pH dependence of root-tip protein synthesis could provide a mechanism that enables the cell's translational machinery to sense changes in pH c , leading directly to selective gene expression. In mammalian cells, a role for cytosolic acidification in signaling programmed cell death is unlikely (Schrode et al, 1997), but changes in cytosolic a K have been implicated (Hughes et al, 1997).…”
Section: The Cellular Mechanism Of Growth Inhibition During K ؉ Starvmentioning
confidence: 96%
See 1 more Smart Citation
“…It was found using cytosolic extracts of Xenopus oocytes that the rates of in vitro translation at pH 7.0 and 6.8 were reduced by approximately 15% and 65%, respectively, relative to pH 7.3 (Grandin and Charbonneau, 1989). Furthermore, a strong pH dependence of protein synthesis has been shown in polyribosome preparations from maize root tips by Webster et al (1991), who suggested that the pH dependence of root-tip protein synthesis could provide a mechanism that enables the cell's translational machinery to sense changes in pH c , leading directly to selective gene expression. In mammalian cells, a role for cytosolic acidification in signaling programmed cell death is unlikely (Schrode et al, 1997), but changes in cytosolic a K have been implicated (Hughes et al, 1997).…”
Section: The Cellular Mechanism Of Growth Inhibition During K ؉ Starvmentioning
confidence: 96%
“…A decrease in cytosolic a K in expanding cells would be expected to diminish rates of protein synthesis, leading to a decrease in the rates of root elongation and dry matter production White, 1993). Changes in pH c have been shown to alter the rate of protein synthesis in both animal (Grandin and Charbonneau, 1989) and plant cells (Webster et al, 1991). To test this hypothesis, pH c and protein synthesis were measured in root tips treated with butyrate or procaine to alter pH c in seedlings growing under K ϩ -starved or K ϩ -replete conditions.…”
mentioning
confidence: 99%
“…The effect of RlPs on translation of endogenous (maize polyribosomal) mRNAs or BMV mRNA (added at 5 pglmL) was then assayed by measuring incorporation of 3H-leucine into protein at 30 min, as previously described (Webster et al, 1991). Micrococcal nucleasetreated wheat germ and rabbit reticulocyte lysates and BMV RNA were from Promega.…”
Section: Ttanslation Lnhibition Assaysmentioning
confidence: 99%
“…We have demonstrated that oxygen deprivation results in the competitive differences between mRNAs for initiation of translation (Fennoy and Bailey-Serres, 1995;BaileySerres and Dawe, 1996). Regulation also occurs after initiation, since certain mRNAs loaded onto polyribosomes are not efficiently translated (Webster et al, 1991;Fennoy and Bailey-Serres, 1995). In yeast, ribosomes lacking P1 and P2 selectively translate a subset of cellular mRNAs, and the www.plantphysiol.org on May 12, 2018 -Published by Downloaded from Copyright © 1997 American Society of Plant Biologists.…”
Section: Oxygen Deprivation Stimulates Dynamic Alterations In the 60smentioning
confidence: 99%